2021
DOI: 10.3389/fcell.2021.660851
|View full text |Cite
|
Sign up to set email alerts
|

The Micro-RNA Cargo of Extracellular Vesicles Released by Human Adipose Tissue-Derived Mesenchymal Stem Cells Is Modified by Obesity

Abstract: Obesity is a chronic disease that interferes with normal repair processes, including adipose mesenchymal stem/stromal cells (ASCs) function. ASCs produce extracellular vesicles (EVs) that activate a repair program in recipient cells partly via their micro-RNA (miRNA) cargo. We hypothesized that obesity alters the miRNA expression profile of human ASC-derived EVs, limiting their capacity to repair injured cells. Human ASCs were harvested from obese and age- and gender-matched non-obese (lean) subjects during ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…Similar data have been obtained in swine [44]. Scientific evidence has indicated that obesity can alter the miRNA content of ASC-derived EVs as well as the ability of these nanoparticles to modulate important injury pathways in the recipient cells [43,45]. Data from human subjects showed that eight miRNAs were upregulated and 75 miRNAs were downregulated in obese EVs vs. lean EVs.…”
Section: Characterization Of Evs Obtained From Ascssupporting
confidence: 74%
See 2 more Smart Citations
“…Similar data have been obtained in swine [44]. Scientific evidence has indicated that obesity can alter the miRNA content of ASC-derived EVs as well as the ability of these nanoparticles to modulate important injury pathways in the recipient cells [43,45]. Data from human subjects showed that eight miRNAs were upregulated and 75 miRNAs were downregulated in obese EVs vs. lean EVs.…”
Section: Characterization Of Evs Obtained From Ascssupporting
confidence: 74%
“…The miRNAs are small single-stranded non-coding RNA molecules (containing about 22 nucleotides) present in all living organisms that function in RNA silencing and posttranscriptional regulation of gene expression. In humans, the literature shows that the size, but not the number, of ASC-derived EVs from obese individuals is smaller than those from lean individuals [43]. Similar data have been obtained in swine [44].…”
Section: Characterization Of Evs Obtained From Ascssupporting
confidence: 62%
See 1 more Smart Citation
“…Differential expression analysis of these EVs allows us to distinguish between lean and obese patients, identifying upregulated miRNAs that mediate the inflammatory response and downregulated miRNAs implicated in cell proliferation and angiogenesis, in obese patients. [168] Castaño et al found that obesity changes the miRNA profile of plasma exosomes in mice, including increases in miR-122, miR-192, miR-27a-3p and miR-27b-3p [73]. Likewise, exosomal miR-20b-5p has been associated with type-2 diabetes in humans [88].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…EVs is the generic term for several subtypes of particles naturally released from the native cells, such as “exosome”, “microparticle/microvesicle”, “ectosome”, “oncosome”, “apoptotic body” and many other names [ 8 ]. With a size of about 50–200 nm, exosome is a subset of endosome-origin small EVs, known as a heterogeneous mixture of microRNA-assembled, protein-decorated and lipid-bound nanoparticles [ 9 11 ]. The last decades has witnessed a dramatically increasing number of scientific publications on ASCs EVs, opening new frontiers for a next-generation drug delivery platform in ASCs-based regenerative [ 10 ].…”
Section: Introductionmentioning
confidence: 99%